The Role of the Capital Market System as a Mechanism for Stability and Economic Growth - Apostolov, Alexander (Research Papers, 2024)
The study provides an overview of the key actors in capital markets and their attendant risks, focusing on a range of transmission mechanisms, resilience, and potential risks to financial stability. It discusses key determinants of the development of modern capital markets and their relationship to economic growth, with an emphasis on the challenges arising from the interconnectedness between banking institutions, the non-bank financial organizations sector, and capital markets. Particular attention is given to the role and importance of government policies, regulatory frameworks, the degree of financial openness, and the institutional environment, in the context of the impact of asymmetric information on capital markets and its implications for investment, financial markets, and their importance in maintaining the stability and transparency of a financial system.